Miles Davis the collected artwork - Davis, Miles 1926-1991 (Insight Ed., 2013)
Throughout the 1980s, Davis studied regularly with New York painter Jo Gelbard, developing a distinct graphic style. Incorporating bright colors and geometric shapes, his art is reminiscent of work by Pablo Picasso as well as African tribal art